Left-right regular elements in HypG(2) - S. Sudsanit (2018)
© 2014 Academic Publications, Ltd. The concepts of a left-right regular element are important role in semigroup theory. In this paper we characterize left-right regular elements of the set of all generalized hypersubstitutions of type τ = (2).